Extracellular Glutamate: Functional Compartments Operate in Different Concentration Ranges - Kalivas, Peter (Frontiers in Systems Neuroscience, 2011)
Tonic extracellular glutamate of glial origin modulates glial and neuronal glutamate release and synaptic plasticity. Estimates of the tonic basal concentration of extracellular glutamate range over three orders of magnitude (0.02-20 µM) depending on the technology employed to make the measurement. Based upon binding constants for glutamate receptors and transporters, this range of concentrations translates into distinct physiological and pathophysiological roles for extracellular glutamate. Here we propose that the difference in glutamate measurements arises from the patterned membrane surface expression of glutamate release and transporter sites creating extracellular subcompartments that vary in glutamate concentration and are preferentially sampled by different technologies. The presence of distinct subcompartments allows extracellular glutamate to selectively regulate different aspects of synaptic plasticity and cell function.